2013
DOI: 10.1021/es404090h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Organic Matter on Iron Uptake by the Freshwater Cyanobacterium Microcystis aeruginosa

Abstract: The mode of Fe uptake by the cyanobacterium Microcystis aeruginosa cultured in Fraquil* (pH 8) containing Suwannee River fulvic acid (SRFA) was examined using short-term radiolabeled (55)Fe uptake assays and a kinetic model that describes extracellular Fe transformations. Both Fe(II) and Fe(III) uptake rates decreased substantially with increasing SRFA concentration as the availability of unchelated Fe decreased due to complexation by SRFA. Fe uptake rates under illuminated conditions were comparable to or sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 54 publications
4
25
1
Order By: Relevance
“…Several reports have suggested that cyanobacteria can extract free iron with high efficiency if free iron is available (Fujii et al, 2010(Fujii et al, , 2011Kranzler et al, 2011), but until now, direct evidence that Fe 0 uptake by cyanobacteria requires TonB-ExbB-ExbD-dependent transport system has been lacking. Although Fe-siderophores can be slowly sequestered by Synechocystis 6803 (Figure 4b), the role of siderophores in iron acquisition by cyanobacteria has probably been overrated in natural water systems (Hopkinson and Morel, 2009;Wirtz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that cyanobacteria can extract free iron with high efficiency if free iron is available (Fujii et al, 2010(Fujii et al, , 2011Kranzler et al, 2011), but until now, direct evidence that Fe 0 uptake by cyanobacteria requires TonB-ExbB-ExbD-dependent transport system has been lacking. Although Fe-siderophores can be slowly sequestered by Synechocystis 6803 (Figure 4b), the role of siderophores in iron acquisition by cyanobacteria has probably been overrated in natural water systems (Hopkinson and Morel, 2009;Wirtz et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some cyanobacteria have tonB-dependent transporters that shuttle iron through the outer membrane (Stevanovic et al, 2012;Kranzler et al, 2013), but there is no evidence of such a function for the tonBdependent transporters identified in Synechocystis 6803 . It is also possible that Fe 0 diffuses through nonspecific porins in the outer membrane (Fujii et al, 2011). Upon entering the periplasm FutA2 binds Fe(III), generating the chemical gradient that facilitates the influx of Fe.…”
Section: Coordinated Transporter Activity C Kranzler Et Almentioning
confidence: 99%
“…Consequently, organically complexed Fe accounts for more than 99.9% of total dissolved Fe in surface seawater (Rue and Bruland, 1995;van den Berg, 1995). Nevertheless, the current consensus on the mode of Fe uptake by phytoplankton suggests that either unchelated Fe (Fe(II) 0 and Fe(III) 0 ) (Morel et al, 2008;Fujii et al, 2014) or Fe(III) bound to low-molecular-weight chelators (van den Berg, 1995) (including siderophores excreted for Fe acquisition under Fe limited conditions) are the major forms available for uptake. The former notion is supported by the fact that the Fe uptake rate depends on the concentration of unchelated Fe buffered by the Fe-binding ligand rather than the total Fe concentration under siderophore-independent Fe uptake, whereas the presence of an active membrane receptor or transporter for the specific form of chelated Fe (e.g., a Fe-siderophore complex) in some microorganisms, including phytoplankton and heterotrophic bacteria, provides evidence for the occurrence of siderophore-mediated Fe uptake (Nicolaisen et al, 2008;Hopkinson and Barbeau, 2012;Fujii et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the current consensus on the mode of Fe uptake by phytoplankton suggests that either unchelated Fe (Fe(II) 0 and Fe(III) 0 ) (Morel et al, 2008;Fujii et al, 2014) or Fe(III) bound to low-molecular-weight chelators (van den Berg, 1995) (including siderophores excreted for Fe acquisition under Fe limited conditions) are the major forms available for uptake. The former notion is supported by the fact that the Fe uptake rate depends on the concentration of unchelated Fe buffered by the Fe-binding ligand rather than the total Fe concentration under siderophore-independent Fe uptake, whereas the presence of an active membrane receptor or transporter for the specific form of chelated Fe (e.g., a Fe-siderophore complex) in some microorganisms, including phytoplankton and heterotrophic bacteria, provides evidence for the occurrence of siderophore-mediated Fe uptake (Nicolaisen et al, 2008;Hopkinson and Barbeau, 2012;Fujii et al, 2014). Marine siderophores are mainly isolated from gamma and alpha proteobacterial cultures and their structures are characterized by amphiphile (e.g., marinobactins and aquachelins) and a-hydroxy carboxylate (alterobactins, pseudoalterobactins and desferrioxamine G) types, both of which often contain hydroxamate and catecholate moieties (Vraspir and Butler, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation